SAT0333 Prevalence of sarcopenia in patients with systemic sclerosis according to the revised criteria of the european working group on sarcopenia in older people. (15th June 2017) - March, C; Siegert, E; Preis, E; Makowka, A; Buttgereit, F; Riemekasten, G; Norman, K
Abstract : Background: Systemic Sclerosis (SSc) is a chronic inflammatory connective tissue disease that is often associated with gastrointestinal involvement and myopathy. Sarcopenia is defined as age-associated loss of muscle mass, strength and function with profound impact on functionality as well as on mortality (1). "Secondary sarcopenia" has now been described in the context of severe and chronic disease such as malignant disease or inflammatory disorders (2) and been linked to poor clinical outcome. Objectives: Analysis of the prevalence of sarcopenia in patients with SSc with respect to clinical characteristics, quality of life and severity of physical impairment. Methods: 129 patients were included. Sarcopenia was defined according to the criteria of the European Working Group on Sarcopenia in Older People (3) using appendicular lean mass assessed by bioelectric impedance analysis and grip strength - stratifying both by body mass index. We also used the 2016 formula by Scafoglieri et.al to calculate appendicular lean mass (4). This approach is different from previous studies because we combined the new formula with established cut-off values, which incorporate a functional parameter. Muscle function was assessed by hand grip, knee extension strength and peak expiratory flow. Impairment and quality of life were evaluated using the Scleroderma Health Assessment Questionnaire (SHAQ) and Short-Form 36 Health Survey (SF-36®). Clinical data were assessed according to standardised procedures. Results: The prevalence of sarcopenia in our study group was 27.1%.There were no significant differences between patients with and without sarcopenia regarding age (p=0.838) and disease duration (p=0.832). There were significant differences regarding grip strength (p<0.001), knee extension strength (p=0.003), peak flow (p=0.042), SF-36® Physical Function (p=0.009) and the number of immunosuppressive (p=0.048) and other drugs taken (p=0.037). See Table 1 . Conclusions: There is a high prevalence of sarcopenia in patients with SSc even among younger patients. Sarcopenic patients have a significant increase in physical impairment and a decreased quality of life regarding their physical health. Taking a higher number of immunosuppressive or other drugs was identified as a risk factor for sarcopenia. This could be due to severe organ involvement being a confounder or an indication for the immunological component in the pathophysiology of secondary sarcopenia. This suggests that sarcopenia might be linked to severe disease or multimorbiditiy in SSc patients. References: Wang C, Bai L. Sarcopenia in the elderly: basic and clinical issues. Geriatrics & gerontology international. 2012 Jul;12(3):388–96. Dogan SC, Hizmetli S, Hayta E et.al. Sarcopenia in women with rheumatoid arthritis. European journal of rheumatology. 2015 Jun;2(2):57–61. Cruz-Jentoft AJ, Baeyens JP, Bauer JM et.al. Sarcopenia: European consensus on definition and diagnosis: Report of the European Working Group on Sarcopenia in Older People. Age and ageing. 2010 Jul;39(4):412–23. Scafoglieri A, Clarys JP, Bauer JM et.al. Predicting appendicular lean and fat mass with bioelectrical impedance analysis in older adults with physical function decline - The PROVIDE study. Clinical nutrition (Edinburgh, Scotland). 2016 Apr 28. Disclosure of Interest: None declared